2002
DOI: 10.1038/nsb845
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization allows DNA target site recognition by the NarL response regulator

Abstract: Two-component signal transduction systems are modular phosphorelay regulatory pathways common in prokaryotes. In the co-crystal structure of the Escherichia coli NarL signal output domain bound to DNA, we observe how the NarL family of two-component response regulators can bind DNA. DNA recognition is accompanied by the formation of a new dimerization interface, which could occur only in the full-length protein via a large intramolecular domain rearrangement. The DNA is recognized by the concerted effects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
192
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(205 citation statements)
references
References 40 publications
11
192
0
2
Order By: Relevance
“…nt, nucleotide. of the two domains exposing critical DNA binding elements in the C-terminal domain (36). By analogy with the NarL activation model, we can speculate that unphosphorylated DesR dimerizes in solution by its C-terminal domain, whereas both N-terminal regulatory domains act as inhibitors of DNA binding by steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…nt, nucleotide. of the two domains exposing critical DNA binding elements in the C-terminal domain (36). By analogy with the NarL activation model, we can speculate that unphosphorylated DesR dimerizes in solution by its C-terminal domain, whereas both N-terminal regulatory domains act as inhibitors of DNA binding by steric hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…35) as a structural template, we found that all of the top 20 DI pairs are true contacts (red bonds in Fig. 4A).…”
mentioning
confidence: 91%
“…The extract (yellow syrup) was purified twice by silica gel chromatography (silica gel 60N, 63-210 mm; Kanto Chemical, Tokyo, Japan; first: 1.5 10 cm gel with hexane/acetone (1:1), second 1.5 20 cm gel with hexane/EtOAc (1:4)) to obtain 282 mg of 25-O-methyl-FD-892. 1 H and 13 C NMR spectra were taken by DRX-500 (Bruker) or ECX500 (JEOL) spectrometer, and FAB-MS spectra were measured by JMS-700 (JEOL). The assignments of and SpeI, and the resulting DNA fragment was inserted into the corresponding site of pCYP-camAB [44] to obtain pGfsF-camAB.…”
Section: Methodsmentioning
confidence: 99%
“…A pOJ446-based cosmid library with the randomly Sau3AI digested genome DNA of S. graminofaciens A-8890 was constructed and further screened by hybridization with the DIG-labeled KS DNAs. As a result, one of the KS gene probes gave a gene cluster containing total 69 kbp of five modular type I PKS genes (gfsA, B, C, D, and E), a cytochrome P450 monooxygenase gene (gfsF), a methyltransferase gene (gfsG), and a NarL family two-component response regulator gene (gfsR), [13] which could be activated by a certain sensor protein in the microorganism ( Figure 1 and Table 1). There is no open-reading frame (ORF) over 1 kbp outside of the gene cluster; this suggests that this gene cluster is one operon for the biosynthesis of this particular polyketide.…”
Section: Identification Of the Gene Clustermentioning
confidence: 99%